Mass Transfer Effects on Unsteady Free Convective Flow Past an Infinite, Vertical Porous Plate with Variable Suction - Kumari, C.V. Ramana; Reddy, N. Bhaskara (Defence Science Journal, 2013)
A two-dimensional unsteady flow of a viscous incompressible dissipative fluid past an infinite, vertical porous plate with variable suction, is studied. Approximate solutions to the coupled non linear equations governing the flow are derived and expressions for the fluctuating parts of the velocity, the transient velocity, temperature and concentration, the amplitude and the phase of the skin-friction, and the rate of heat transfer, are derived. The effects of w(Omega)(frequency), Gr (Grashof number), Gc (modified Grashof number), Sc (Schmidt number), P (Prandtl number) and A (variable suction parameter), on the above physical quantities are calculated numerically and presented in figures and table. Problems of this nature find place in ablative cooling, transpiration and film cooling of rocket and jet engines.